Country Partnership Framework for the Republic of Indonesia for the Period FY21 - FY25 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (Washington, DC: World Bank, 2021)
This document presents the Country Partnership Framework (CPF) for the World Bank Group (WBG) for Indonesia, covering the period FY2021-FY2025. The CPF builds on past successes and blends continuity of the past strategy with change. The past strategy began shifting towards supporting private sector-led growth, based on investments in human capital and underpinned by institutional reforms. This CPF proposes a further shift towards reinforcing fiscal resilience, harnessing the potential of digitalization, integrating climate change considerations, and realizing the contribution of gender to promote a resilient recovery from the pandemic and long-term economic growth. Current conditions require re-focused knowledge and advisory work, inter alia, in public finances, governance, health and social protection as well as a rise in the volume of IBRD lending and IFC financial support tilted towards these re-defined priorities. This document details the CPF program for the first three years of the CPF period in light of unusually great uncertainties, within a five-year overall framework. The first half of the CPF period will be dominated by the need to secure a sustained recovery from the COVID pandemic.